Perilaku Kesehatan Penderita Hipertensi - Firyal Tsamarah Salsabila; Beti Kristinawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research explores the health behavior of hypertension sufferers in coastal areas, especially in Ketapang District, South Lampung Regency, Lampung Province. This study uses a qualitative method with a narrative approach with unstructured interviews. The research results identified seven main themes: food and drink consumption patterns at risk of hypertension, smoking habits, lack of physical activity, poor stress management, use of hormonal contraceptives, non-compliance with antihypertensive drug therapy, and routine blood pressure checks. Conclusions from the statements of twenty-seven informants who experience hypertension: they have health behaviors that are at risk of hypertension in the form of food and drink consumption patterns that are at risk of hypertension, active and passive smoking habits, lack of physical activity, poor stress management, non-compliance with drug therapy antihypertensives, and some check their blood pressure regularly and also those who do not have their blood pressure checked periodically. Keywords: Hypertension, Health Behavior, Coastal, Qualitative Study